The effectiveness of e-booklet and lectures to increase overweight adolescents’ nutritional knowledge - Suminah Suminah; Veronika Ika Budiastuti; Reri Noor Amelia (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Overweight adolescents’ low knowledge of balanced nutrition is a problem that needs attention. If such a problem is left unchecked, overweight adolescents have a higher risk of suffering from various health problems. Efforts are needed to increase overweight adolescents’ nutrition knowledge, including through the provision of nutrition education using educational media. The purpose of this study was to analyze differences in knowledge after being given nutrition education using e-booklets and lectures. This study was conducted at SMAN 4 and SMAN 7 Banjarmasin in September 2022. This study was an experimental research with a quasi-experimental design with pre-test – post-test control group. The sample in this study was selected by purposive sampling technique, namely 64 overweight students divided into two groups, namely nutrition education with e-booklets accompanied by lectures and nutrition education with lectures only. The intervention was carried out 4 times in one month and each meeting took 55 minutes. Data on differences between pretest and posstest were analysed by paired T Test and data on differences between education groups were analysed by Independent T Test. Results, there were differences in pretest and posttest nutritional knowledge in groups given nutrition education with e-booklet media and lectures (p=0,000) and there are differences in groups given nutrition education with lectures only (p=0,001). There was a significant difference effect between the provision of nutrition education in both education groups (p=0,002). In conclusion, providing nutrition education with e-booklet media combined with lectures can improve knowledge about balanced nutrition for overweight adolescents more effectively than lectures.